Policy regimes and industrial competitiveness a comparative study of East Asia and India - Agrawal, Pradeep; Gokarn, Subir V; Mishra, Veena (Houndmills Macmillan Press, 2000)
This book looks at the economic performance of East Asia in a Unified way.The framework used allows us to identify the separate roles of macroeconomic and microeconomic factors,and to understand how they interacted with one another. The basic lesson of th
Keywords: East Asia-Commerical policy; India-Commmerical policy; Monetary policy-East Asia; Monetary policy-India; Labour policy-East Asia; Labour policy-India; Indusrtial policy-East Asia; Industrial policy-India; Competition,International